2012
DOI: 10.1089/pho.2011.3043
|View full text |Cite
|
Sign up to set email alerts
|

Topical Grape Seed Proanthocyandin Extract Reduces Sunburn Cells and Mutant p53 Positive Epidermal Cell Formation, and Prevents Depletion of Langerhans Cells in an Acute Sunburn Model

Abstract: GSPE may be a possible preventive agent for photoprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In contrast, GSPs enhanced the production of immune stimulatory cytokine IL-12 in the draining lymph nodes. GSPs fed mice exhibit a reduction in UV-induced suppression of allergic contact hypersensitivity, a prototypic T-cell-mediated response [51]. Results suggest that GSPs prevent UVB-induced immunosuppression through DNA repair dependent functional activation of dendritic cells and reexpression of tumor suppressor genes RASSF1A , p16INK4a , and Cip1/p21 .…”
Section: Skin Cancer Chemoprevention By Using Phytochemicals: Mechmentioning
confidence: 99%
“…In contrast, GSPs enhanced the production of immune stimulatory cytokine IL-12 in the draining lymph nodes. GSPs fed mice exhibit a reduction in UV-induced suppression of allergic contact hypersensitivity, a prototypic T-cell-mediated response [51]. Results suggest that GSPs prevent UVB-induced immunosuppression through DNA repair dependent functional activation of dendritic cells and reexpression of tumor suppressor genes RASSF1A , p16INK4a , and Cip1/p21 .…”
Section: Skin Cancer Chemoprevention By Using Phytochemicals: Mechmentioning
confidence: 99%
“…The creams developed from grape seed extracts were considered safe and nonirritating to the skin in the Burchard test [67]. Skin treated with grape seed extract before UV exposure showed less p53 mutant cells and more epidermal cells and Langerhans cells compared to untreated skin [68], suggesting greater protection of the human genome against photoaging, mutations, and skin cancer [69]. A study carried out with 22 winegrowers showed a weak positive reaction in six individuals who worked directly on grapevines.…”
Section: Discussionmentioning
confidence: 99%
“…Proanthocyanidins are effective antioxidants and anti-inflammatory agents found in particularly high concentrations in grapes (GSPs) [60]. GSPs have been found to reduce UV skin damage, like photo-aging, and to decrease melanin synthesis [121, 122]. .In humans, GSPs have been shown to reduce mutant p53-positive epidermal cells and prevent the depletion of Langerhans cells after sunburns.…”
Section: Nutrients/phytochemicals and Melanomamentioning
confidence: 99%